Alice and the assassin - Koreto, Richard J. (Koreto, Richard J. Alice Roosevelt mystery., 2017)
In 1902 New York, Alice Roosevelt, the bright, passionate, and wildly unconventional daughter of newly sworn-in President Theodore Roosevelt, is placed under the supervision of Secret Service Agent Joseph St. Clair, ex-cowboy and veteran of the Rough Riders. St. Clair quickly learns that half his job is helping Alice roll cigarettes and escorting her to bookies, but matters grow even more difficult when Alice takes it upon herself to investigate a recent political killing--the assassination of former president William McKinley. Concerned for her father's safety, Alice seeks explanations for the many unanswered questions about the avowed anarchist responsible for McKinley's death. In her quest, Alice drags St. Clair from grim Bowery bars to the elegant parlors of New York's ruling class, from the haunts of the Chinese secret societies to the magnificent new University Club, all while embarking on a tentative romance with a family friend, the son of a prominent local household. And while Alice, forced to challenge those who would stop at nothing in their greed for money and power, considers her uncertain future, St. Clair must come to terms with his own past in Alice and the Assassin, the first in R. J. Koreto's riveting new historical mystery series.